Perceptions and beliefs on sports injury prediction as an injury risk reduction strategy: An online survey on elite athletics (track and field) athletes, coaches, and health professionals - Dandrieux, P.-E.; Navarro, L.; Chapon, J.; Tondut, J.; Zyskowski, M.; Hollander, K.; Edouard, P. (Physical Therapy in Sport, 2024)
Objectives To explore perceptions and beliefs of elite athletics (track and field) athletes, coaches, and health professionals, towards the use of injury prediction as an injury risk reduction strategy.